INAPPROPRIATE REQUESTS FOR TUMOR MARKERS IN PATIENTS AGED 50 YEARS AND OLDER: LESSONS NOT LEARNED - Valter Paz Nascimento-Júnior; Einstein Francisco Camargos (Brazilian Society of Geriatrics and Gerontology, 2021)
OBJECTIVE: To investigate, within a private health insurance, the ordering frequency and the costs related to inappropriate tumor markers test orders. METHODS: This study analyzed data regarding tumor markers requests within a private health insurance between 2010 and 2017. Patients included in this analysis were ≥ 50 years old, had available medical records, and had at least 1 tumor markers tested within the study period. Tests were considered inappropriate when tumor markers were used in screening for neoplasms, ie, when there was no previous diagnosis. We evaluated data regarding age, sex, the ordering physician's medical specialty, and test costs. RESULTS: Between 2010 and 2017, 1112 tumor markers tests were performed and increased from 52 to 262 per year. Our sample consisted mostly of women (69.50%) with a mean age of 59.40 (SD 8.20) years. Most orders were inappropriate (87.80%) and represented 79.40% of all expenses with tumor markers tests. Cardiology professionals were the medical specialty that requested the most tumor markers tests (23.90%), followed by internal medicine specialists (22.70%) and gynecologists (19.20%). CONCLUSIONS: We observed a high percentage of inappropriate test orders in the study period, resulting in elevated costs. Studies of this nature deserve the attention of health care managers, and interventions should be performed in order to reduce the inappropriate use of tumor markers tests in clinical practice.